A Review of Advances in Bioanalytical Methods for the Detection and Quantification of Olanzapine and Its Metabolites in Complex Biological Matrices - Anna Czyż; Alicja Zakrzewska-Sito; Julita Kuczyńska (Pharmaceuticals, 2024)
Schizophrenia is a serious mental disorder that significantly affects the social and professional life of patients, causing distortion of reality and loss of identity and cognitive abilities. Psychopharmacological treatment is an integral part of modern psychiatry, and the introduction of new “atypical” antipsychotic drugs has brought significant progress in the treatment of this disorder. One of these drugs is olanzapine, which has an effective effect on the productive symptoms of schizophrenia while having an almost minimal potential to cause extrapyramidal syndrome. However, its effectiveness is confronted with frequent side effects, referred to as “metabolic disorders”. Therefore, to ensure the effectiveness of treatment and to minimize the side effects caused by olanzapine, it is recommended to monitor the drug level during therapy. This article reviews the bioanalytical methodologies that enable efficient extraction and sensitive analysis of olanzapine. We considered the advantages and disadvantages of different sample pretreatment methods, including traditional and novel strategies. The analytical conditions required for the separation and detection of olanzapine and its metabolites were analyzed using chromatographic methods combined with various detectors.